Comparative utility of biochemical markers for differentialdiagnosis of ascites - Anchinmane, Vyankatesh T.; Sankhe, Shilpa V. (International Journal of Research in Medical Sciences, 2016)
Background: Ascites is pathological accumulation of free fluid in the peritoneal cavity. Appropriate management for ascites depends upon diagnosis of its etiology. Based on total protein concentration of ascitic fluid, earlier ascites was classified as transudate and exudate. The present study was designed to compare the utility of total protein, lactate dehydrogenase (LDH) and serum ascites albumin gradient (SAAG) to categorise ascitic fluids as either exudate or transudate. Methods: This prospective study comprised of 110 adult patients with ascites whose diagnosis was established by clinical examination and appropriate investigations. Biochemical analysis of ascitic fluid and serum was done with protein, albumin and LDH. The usefulness of each biochemical parameters was statistically evaluated in terms of sensitivity, specificity, accuracy, PPV and NPV. Results: In this endeavour, the SAAG and fluid LDH did showed a clear advantage over the fluid protein which is traditional existing biochemical parameter for differential diagnosis of ascitic fluid into transudate and exudate. Conclusions: The SAAG had more discriminatory power than fluid protein parameter and hence should replace fluid protein test in diagnostic separation of ascites into transudate and exudate.